Analisis Aksiologi Filsafat Islam dalam Penanaman Adab Santri di PPTQ Nurul Iman - Suyatman, Suyatman; Supono, Eko; Mujiburrohman, Mujiburrohman (TSAQOFAH, 2025)
This study aims to analyze the axiological values of Islamic philosophy in the process of instilling adab (ethical conduct) among students (santri) at Pondok Pesantren Tahfidzul Qur’an (PPTQ) Nurul Iman. The research is grounded in the understanding that adab plays a fundamental role in shaping students’ character and morals, while also serving as a practical implementation of Islamic philosophy, which emphasizes harmony between knowledge, values, and action. A descriptive qualitative method was used, with data collected through observation, in-depth interviews, and documentation. Data analysis followed the stages of data reduction, data display, and conclusion drawing. The findings show that the application of axiological values of Islamic philosophy is reflected in the habituation of polite behavior, respect for teachers, discipline, responsibility, and self-control. Supporting factors include the exemplary conduct of ustadz/ustadzah, a conducive pesantren environment, and the integration of Islamic values within the curriculum and daily activities. Challenges identified include the influence of digital culture, diverse student backgrounds, and consistency in supervision. The study concludes that instilling adab based on the axiology of Islamic philosophy at PPTQ Nurul Iman significantly contributes to the formation of well-mannered, knowledgeable, and virtuous students, though adaptive strategies are needed to address the challenges of the modern era.